The error in the steps is that In step 1, she should have also distributed -3/8 over –16d, to get 3 + 6 d + 2 d = 24
<h3>Simplifying linear equations</h3>
Given the following equation as shown below
-3/8(-8-16d)+2d = 24
Step 1 Distribute -3/8 over the expression in parentheses
3 + 6d + 2d = 24
Simply the like terms
3 + 8d = 24
Subtract 3 from both sides of the equation.
8d = 24 - 3
8d = 21
d = 21/8
Hence the error in the steps is that In step 1, she should have also distributed -3/8 over –16d, to get 3 + 6 d + 2 d = 24
Learn more on linear equation here: brainly.com/question/1884491
#SPJ1
Day 1: 8km=4.97miles
Day 2: 10miles=16.09km
Day 3: 9miles=14.4km
9.6km=5.9miles
I really hope this helps! Not really sure what exactly the answer you are looking for is but this should help you figure it out
Answer:
h(2) = 5.2 + 1 = 10 + 1 = 11